PENGARUH PEMUPUKAN DAN PEMANGKASAN TANAMAN TERHADAP PRODUKTIVITAS DAUN MURBEI DI KOTA TOMOHON, SULAWESI UTARA - Lis Nurrani; Supratman Tabba; Andi Wildah (Jurnal Pemuliaan Tanaman Hutan, 2019)
Mulberry is an important feed for increasing the productivity in cocoons on silkworm cultivation. Mulberry having a high nutrition is very important. This is because the nutritional value is the most important factor influencing the quality and quantity of cocoons and silk. Therefore, the development of improved mulberry accompanied with an appropriate cultivation technique is necessary. This study aims to determine the effect of fertilization and trimming on the leaves productivity of three species of mulberry planted in a demonstration plot in Rurukan, Tomohon, North Sulawesi. The three species of mulberry used in this study are mulberry of SULI 01, Morus cathayana and M. canva which were tested under three types of fertilizer: Taikam, Petroganik and manure. The trimming test was only practiced for the two species of M. cathayana dan M. canva with three trimming height of 30 cm, 45 cm and 60 cm above the ground. All the tests were arranged under a completely randomized factorial design. The genetic materials of mulberry were supplied from Forest Productivity Research and Development Center in Bogor. The measured parameters were diameter and height of plant, and leaves production. The results showed that in general the fertilization had no effect on leaves productivity for all of the tested species of mulberry. The application of Taikam and manure only affected the growth of diameter and height of mulberry plant. The trimming treatment provided a difference of leaves productivity between the two species of mulberry. The highest leaf production for M. canva (639.61 gr) was found at trimming of 45 cm, while for M. cathayana was found at trimming of 60 cm (482.40 gr).